Comprehensive integration of mass and energy utilization for refinery and synthetic plant of chemicals. (15th February 2023) - Yang, Yang; Zhang, Qiao; Feng, Xiao
Abstract: Expensive industrial mass and energy mediums, including hydrogen, carbon oxides, and steam, heat and electricity derived from resources of coal, and/or petroleum and/or natural gas, are extensively consumed in refinery and synthetic plant of chemicals (SPC) to simultaneously manufacture value added products and generate emissions. Mass is the carrier of energy while energy is the driving force of mass conversion. Based on such dialectical relationship in chemical conversions, a mass and energy comprehensive integration methodology is proposed to minimize resource consumption and carbon emission. A hierarchical superstructure consisting of resources to intermediate feedstocks (IFs) and IFs to final conversions for refinery and SPC is constructed and a mixed integer non-linear programming (MINLP) model is established to perform optimization. Case study results indicate that with intact productivity as individual networks, comprehensive integration can conserve coal consumption by 23.9%, natural gas consumption by 7.6% and total CO2 emission by 14.4%. The methodology in this work demonstrates that the interaction of mass and energy in chemical conversions is crucial to resource conservation and emission reduction and thus comprehensive integration is great progress in process integration. Highlights: Refinery and synthetic plant of chemicals (SPC) coupling network integration methodology. A two-stage superstructure is put forward to configure resources, IFs and products hierarchy. Mass-energy interaction based optimization for resource conservation and emission reduction.